Radiological impact assessment of fukushima daiichi nuclear accident on Malaysian Marine biotas via Ocean Partway using Erica Code System - Hoh, Siew Sin; Sukiman Sarmani; Khoo, Kok Siong (Universiti Kebangsaan Malaysia, 2014)
Fukushima Daiichi nuclear disaster led to radioactive contamination crisis was resulted from a series of system failures, nuclear meltdown and radioactive material releases, following the 9.0 magnitude of earthquake and tsunami on March 11, 2011. The objectives of this study were; to investigate the movement of radionuclides based on oceanography and morphology of Pacific Ocean and Southeast Asia (Malaysia); to estimate the time for radionuclides to reach Malaysia and to calculate the amount of total absorbed dose rate for selected marine biotas namely benthic fish and pelagic fish. ERICA code system was used because it has the ERICA integrated approach to assess the radiation risk of biota. The estimations of radionuclide discharge from Fukushima Daiichi nuclear disaster were based on Cs-137 (half-life of 30.17 years), I-131 (half-life of 0.02 years). The parameters such as discharge rate of radionuclides (Bq/s), water depth (m), the distance between the target coast of Malaysia and radionuclide release point (m), the distance between the receptor and radionuclide release (m) and the velocity of the water/ocean currents (m/s) were studied. The results showed that the minimum estimated arrival time of radionuclides to reach Malaysia is located in Sandakan, Sabah, which is approximated at 4.82 years (Dec 2015) with an average of 5.039±0.310 years after the accident. Meanwhile, maximum estimated arrival time of radionuclides to Malacca is 5.87 years (Jan 2017) with an average of 5.527±0.480 years. The lowest estimated total absorbed dose rate by benthic fish is 0.0583 μGy/h with an average of (6.33±0.71) × 10-2 μGy/h in Malacca whereas the highest estimated total absorbed dose rate by benthic fish is 0.0751 μGy/h with an average of (7.11±0.57) × 10-2 μGy/h in Sandakan, Sabah. Pelagic fish in Malacca shows the lowest estimated total absorbed dose rate of 0.00149 μGy/h with an average of (1.62±0.18) × 10-3 μGy/h whereas Sandakan, Sabah showed the highest estimated total absorbed dose rate of 0.00193 μGy/h with an average of (1.83±0.15) × 10-3 μGy/h. The total absorbed dose rate and risk quotient of ERICA code system show that for all reference organisms, the probability of exceeding the selected screening dose rate of 400 μGy/h by aquatic biota is below the probability selected. Therefore, no measurable population of chronic exposure effects would occur at this stage. Nonetheless, a normal experimental analysis of fish samples should be performed in order to monitor the radiation effects to marine ecosystem.